Effect of Heat Exposure on Percentage of Dead Sperm and Pyriform Cell in Male New Zealand White (NZW) Rabbit - Kasa, I Wayan (Metamorfosa: Journal of Biological Sciences; Vol 5 No 2 (2018), 2018)
Experiment has been done on the effect of heat exposure on the percentage of dead sperm and pyriform cell in male NZW rabbit. The bucks were exposed to 34°C for 8 hours on either 1 or 5 days. It was found that scrotal temperature (ScT) increased very rapidly during the first hour of exposure by 4°C in group 1 (1x8h). In group 2 (5x8h of exposure) ScT differed significantly between days (P < 0.05). The bigest response was on day 1 (36.6°C) and followed a progressive reduction, day by day, in an apparent acclimation pattern. At different times of exposure, ScT was observed to rise rapidly during the first hour (by 14 percent or 4.4°C). In the 1x8h treatment dead sperm achieved a maximum level of 14.5 ± 4.7 percent in the first week after hotroom treatment. In week 2, the percentage dead sperm started to decline. When rabbits were exposed to 5x8h, this group was more severely affected than the 1x8h. In week 1, the percentage dead sperm in the 5x8h group was 2.1 fold greater than in the 1x8h group (31.0 vs 14.5 percent). Recovery in the 5x8h group took longer than in the 1x8h group, and the percentage dead sperm finally returned to normal levels only after 7 weeks, compared to 5 weeks after 1x8h treatment.Between weeks, the incidence of pyriforms did differ significantly (P < 0.05). In the 1x8h treatment, the percentage pyriforms increased in the first week after hotroom exposure by 3.8 percent. In week 2, the percentage pyriform started to decline and continued to do so gradually until week 6. In the 5x8h treatment, the number of pyriforms was higher than it was in 1x8h treatment. In week 1, for example, the percentage pyriform was 16 percent higher than in 1x8h treatment group. Hence, the mean pyriform cell count was 1.6 times higher in the 5x8h compared to the 1x8h group.